Adherence to drug treatment in patients with hypertension with very high cardiovascular risk - Vizir, V. A.; Sadomov, A. S.; Demidenko, O. V.; Візір, Вадим Анатолійович; Садомов. Антон Сергійович; Деміденко, Олександр Вікторович (My University, 2024)
The aim of the study was to evaluate the adherence to treatment of patients with HTN with very high total CRP when using polypill.